Research progress on humanistic nursing needs of elderly patients regarding nebulized therapy (老年雾化吸入患者人文护理需求研究进展) - ZHANG Mingjiao (张明娇); LI Yufeng (李玉凤); LI Xingya (李星娅); WANG Ran (王然) (中西医结合护理)
Nebulized therapy has been wildly used in the treatment of respiratory diseases. As a core competence of clinical medical workers, humanistic nursing aims to provide greater coverage and assistance to clinical health service. This article reviewed studies on humanistic care needs of elderly people regarding nebulized therapy, and analyzed the influencing factors of humanistic care ability of clinical nurses. It aims to provide reference for improve the humanistic care ability of nurses in clinical practice. (雾化吸入是呼吸系统疾病重要的治疗手段。人文关怀是医护人员必备的基本素养, 是护理工作的扩充和延伸。本文总结老年雾化吸入患者人文关怀需求现状, 分析影响护士人文关怀能力的影响因素, 以期为提升护理人员人文关怀能力提供参考。)